Traffic jam - Cheng, Shu-fen ([Heryin Books], 2013)
When a family hits traffic on the way home, the daughter sees some fascinating scenery: underwater elevators, pearl necklaces, a whale policeman
Keywords: Bilderbuch; Traffic congestion / Juvenile fiction; Straßenverkehr; Unterwasserwelt; Fantasiereise; Verkehrsstau